Occupational mismatch and moonlighting among Spanish physicians: do couples matter? - Juan José Dolado; Florentino Felgueroso (Institute for the Study of Labor (IZA), 2008)
There are relevant gender differences in the labour-market status of health sciences graduates in Spain: (i) female physicians have lower participation rates than male physicians plus they are subject to higher occupational mismatch, and (ii) moonlighting is more frequent among male physicians. In this paper we investigate whether such differences are related to the monopsonistic features of the labour market of health-care professionals. This provides an interesting case study since, among all university graduates, Spanish physicians are the ones most often coupled to partners with the same educational level and/or same type of studies.
urn:nbn:de:101:1-2008040147
Keywords: J42; 330; Monopsony; physicians; mismatch; moonlighting; gender; Arbeitsmarkt; Ärzte; Männer; Frauen; Strukturelle Arbeitslosigkeit; Nebentätigkeit; Spanien